Crosslinguistic effects at the conceptual level: How cognitive linguistics can inform transfer research - Franka Kermer (Poland, 2022)
This paper attempts to offer a state-of-the-art review of recent works that address crosslinguistic influence at the conceptual level from the viewpoint of cognitive linguistics. The recent interest in and growth of empirical evidence of a cognitive-oriented analysis of crosslinguistic influence has led to the emergence of an entirely new line of research on mother tongue influence. This review presents points of divergence between cognitive linguistics on the one hand and conceptual transfer on the other, thereby surveying numerous notions within cognitive linguistics that can aid transfer research. The notions that are paid attention to are conceptualization, categorization, and construal. This also gives an idea of what cognitive linguistics is able to contribute to research on second language acquisition more generally. The second aim of the paper is to point to empirical works that investigate crosslinguistic influence through the lens of cognitive linguistics, thereby highlighting how and to what extent speakers’ conceptual representations and cognitive patterns that are prevalent in their L1 influence the acquisition and use of conceptual structures in their L2. Taken collectively, the empirical findings of these studies give rise to the advantageous effect of employing a comprehensive and sophisticated account of language to the study of how conceptualizing systems in speakers who use two or more languages influence one another.